1992
DOI: 10.1001/jama.1992.03480200077028
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Disease Stage and Zidovudine Therapy on the Detection of Human Immunodeficiency Virus Type 1 in Semen

Abstract: HIV-1 is more commonly found in semen from men with advanced HIV-1 infection and seminal leukocytosis but can also be cultured from semen of men with neither of these conditions. Zidovudine therapy may decrease the prevalence and/or titer of seminal HIV-1. However, all HIV-1-infected persons should continue to assume that they are potentially infectious through sexual contact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
1

Year Published

1992
1992
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(32 citation statements)
references
References 25 publications
3
27
0
1
Order By: Relevance
“…Our study also confirmed a positive association between seminal leucocytosis and HIV-1 in semen, as reported in previous studies [2,25]. From the present study, it could be concluded that there exists a clear association between leucocytospermia and HIV infection.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study also confirmed a positive association between seminal leucocytosis and HIV-1 in semen, as reported in previous studies [2,25]. From the present study, it could be concluded that there exists a clear association between leucocytospermia and HIV infection.…”
Section: Discussionsupporting
confidence: 93%
“…Semen is an important vehicle for sexual transmission of HIV-1 [9], yet relatively little is known about the frequency and location of HIV within semen or its constituents [16,25]. Epidemiologic studies indicate that HIV-1 transmission via semen to sexual partners occurs with varying degrees of efficiency [2]. Conflicting reports exist with regard to effects of HIV on sperm characteristics [1,9,10].…”
Section: E Umapathy Et Almentioning
confidence: 99%
“…HIV-1 levels in semen have been associated with LCS (33,34). More recently, Krause and colleagues (12) compared the prevalence of CMV, EBV and HSV antibodies in serum of men with and without LCS.…”
Section: Introductionmentioning
confidence: 99%
“…1,5 ART may decrease the likelihood of further HIV transmission by reducing circulating levels of HIV RNA. [7][8][9][10][11][12][13][14][15][16] Treatment of other sexually transmitted diseases (STD) and coinfections [17][18][19][20][21][22] may also decrease the likelihood of further HIV transmission. In addition, care providers can help promote safer behaviors among their HIV-infected clients.…”
mentioning
confidence: 99%